Pengaruh Struktur Aset, Profitabilitas, dan Pertumbuhan Penjualan terhadap Struktur Modal pada PT Industri Jamu dan Farmasi Sido Muncul TBK Periode 2014-2024 - Nur Annisa; Asep Muhammad Lutfi (Pajak dan Manajemen Keuangan, 2026)
This study aims to examine the effect of Asset Structure, Profitability and Sales Growth on Capital Structure at PT Industri Jamu Dan Farmasi Sido Muncul Tbk for the 2014-2024 period, both partially and simultaneously. Asset structure is measured by total assets, profitability is measured by return on assets, sales growth is measured by sales growth, and capital structure is measured by debt to equity ratio. This study is a quantitative study with an associative approach. The data used in this study are the balance sheet and income statement of PT. Industri Jamu Dan Farmasi Sido Muncul Tbk for the 2014-2024 period. The method used in this study is multiple linear regression analysis techniques, classical assumption tests, t-tests, f-tests and coefficients of determination processed using the SPSS 26 program. The results of the study show that asset structure does not affect capital structure with a calculated t value of 2.288 t table 2.365. Sales growth does not affect the capital structure with a calculated t value of -0.203 < t table 2.365. And simultaneously, Asset Structure, Profitability and Sales Growth have an influence on the Capital Structure of the Company PT Industri Jamu Dan Farmasi Sido Muncul Tbk. Proven from the results of the f test, the calculated f value is 8.083 > f table of 4.35 and the sig value is 0.011 < 0.05.